The doctrine of scripture: an introduction - Thompson, Mark D. (Short Studies in Systematic Theology Ser., 2022)
Centered in the words of Scripture and especially the teaching of Jesus himself, this volume unpacks the doctrine of Scripture as taught by the church through the ages, helping to strengthen readers' confidence in God's word.